Effects of 16 weeks of strength and plyometric training on physical performance in semiprofessional soccer players - Otero-Esquina, C.; Pareja-Blanco, F.; Rodriguez-Rosell, D.; Gonzalez-Badillo, J. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
There are several studies which have evaluated the effects of strength training over jump height and acceleration capacity with soccer players using loads >85% 1RM until failure (1,3). However, to our knowledge there have not been any studies that evaluate the effects of training with lower loads and not to failure in semi-professional soccer players. Therefore, the aim of this study was to analyze the effects of this type of training on physical performance. Method: Fifteen soccer players from third Spanish division took part in this study (age 22.7±3.4 years, height 1.78±0.06m, weight 75.4±6.8kg). These subjects completed a strength training twice a week for 16 weeks. Subjects performed full squat (4-8 reps 40-60% 1RM), CMJ with and without load, resisted sprint and loaded change of direction. The variables measured were: estimated 1RM full squat (T-Force System), CMJ height and acceleration capacity in 10 and 20m (T10, T20 and T10-20). A related-samples ttest was used to analyse pre-post changes among variables and correlation was determined through Pearson`s coefficient correlation. Results: Subjects obtained significant improvements in CMJ height (5.5%; p<0.01), T10-20 (0.8%; p<0.05) and estimated 1RM full squat (7.4%; p<0.05) while T10 and T20 showed no significant changes. Pretest values found significant correlations (p<0.05-0.01) between CMJ and T10 (r= -0.69), T10-20 (r= -0.59), T20 (r= -0.74) while RM correlated significantly (p<0.05) with T10 (r= -0.53) and T20 (r= -0.57). However, post-test showed stronger correlations between CMJ and 1RM (r= 0.61), T10 (r= -0.75), T10-20 (r= -0.72) and T20 (r= -0.78). Discussion: These results show that plyometric and strength training with light loads (40-60% 1RM) and not to failure (4-8 reps) improve 1RM full squat, CMJ height and T10-20 which are very important for soccer successful (1). These findings show higher gains on performance than other works (3), which did not show changes neither CMJ nor sprint time training with high loads until failure. Therefore, the present study suggests that is not necessary to train with high intensity (% 1RM) to improve soccer players performance.